Manajemen Program Bina Prestasi dalam Meningkatkan Potensi Siswa pada Lembaga Pendidikan Islam - Kamila, Nuha Ghina Zulfa; Mustofa, Triono Ali (Fitrah: Journal of Islamic Education, 2023)
The Bina Prestasi program in Islamic educational institutions is growing, therefore it needs good management so that students get the right to foster achievement in order to increase student potential. This study aims to analyze the management of the Bina Prestasi program in increasing student potential, as well as the supporting and inhibiting factors of Bina Prestasi program management at Al-Irsyad Junior High School in Surakarta. This research uses a qualitative method with a phenomenological approach. Data collection used observation, interviews and literature study. Data analysis used data reduction, data presentation, and conclusion drawing. The results of this study found that the achievement development program of Al Irsyad Junior High School Surakarta through the fields of natural science, social science, mathematics, English, Indonesian, Arabic, Khitobah, Calligraphy, Ziyadah, MHQ, and MTQ. The target is that each subject must include students in at least two competitions in one semester. Supporting factors are good cooperation and performance of all parties, effective and efficient utilization of funds, and adequate infrastructure. The inhibiting factor is that student enthusiasm sometimes fluctuates, and the material taught must be updated and upgraded.